Late and multifocal presentations of malignant peripheral nerve sheath tumours following radiotherapy. (7th July 2015) - Jones, Lara; Bradley, Lloyd
Abstract : Peripheral nerve sheath tumours are a well-recognised complication of radiotherapy. Single tumours presenting up to 10 years after initial treatment have been previously described. We report an individual with two anatomically separate nerve sheath tumours developing at different time intervals following initial treatment, after 38 and 42 years, respectively. This case illustrates the importance of maintaining vigilance for the development of complications even at an advanced stage following index radiotherapy treatment.